Design Of Ankle Foot Orthosis (Afo) Using 3d Printing For Patient Comfort And Agility - Ong, Xhin Jie (Universiti Sains Malaysia, 2019)
Ankle-foot orthosis is a medical device worn to assist the daily mobility of patients suffering from ankle-foot deformity as a result of stroke or accident. However, the available product in the market was costly, and the design was not suitable for local patients due to the hot and humid tropical climate. The current available product also does not fit very well to specific patient’s foot profile, resulting in discomfort and therefore less usage by patient. The purpose of this research was to design of a new ankle-foot orthosis (AFO) using 3D printing for patient comfort and agility. The prototype design was created using SolidWorks. Then, static analysis was applied to the assembled AFO model using SolidWorks to determine the responses of parts and assemblies in the form of stress, displacement and strain when the external loads were applied in the assembled model. The material used in the fabrication of prototype was PLA and fabricated using Anycubic I3 Mega 3D printer. Besides, gait testing and analysis were done for five different walking conditions to find out the difference angle measurement of the gait cycle between wearing and non-wearing AFO. Two sets of comparison result were discussed, which were the comparison between the current and new product, and the comparison of angle measurement between wearing and non-wearing AFO. Lastly, some suggestions were given for future work.